MENGGIATKAN TAMAN BACAAN MESJID BAGI REMAJA MESJID - Linzzy Putri; Lila Bismala (JURNAL PRODIKMAS Hasil Pengabdian Kepada Masyarakat, 2017)
This activity aims to build and give training on mosque library management so that teenagers and children around the mosque can channel their hobbies in reading rather than playing. Activity begins with determineing what books are needed, then to organize the library of the mosque, so that library management can run well, accompanied by formulating regulations that will be applied. Organizing is done by sorting the book, such as the book of prophets and apostles, books of Fiqh and other religious knowledge